Does Parental Involvement Contribute to Students’ Development? The Parent-Child Homework Experiment at a Shanghai Migrant School - Li, Jiacheng; Li, Yan; Yin, Tingting (International Journal about Parents in Education, 2023)
Migrant students’ education and well-being are the hot-button issues in Chinese education. Collaboration between parents and teachers to support migrant students is greatly needed. The purpose of this research is to better understand the influence of parental involvement on the development of the students through findings from the Parent-Child Homework Project at a migrant school in Shanghai, China from December 2013 to June 2015. This paper explores the following research questions: What are migrant students’ perceptions and experiences in the Parent-Child Homework Project (PCHP), what have the migrant children gained from the PCHP by working with the parents directly, and how do teachers evaluate the PCHP? The authors distributed 362 student questionnaires, interviewed 8 teachers and 28 parents, and visited the parent-child homework show. The authors find that the migrant students highly valued the parent-children homework, and demonstrated improvement in aspects of academic, emotional and social development. Parent and teachers value the project too. The paper discusses the collaboration between teachers and migrant parents, and puts forward some suggestions to make additional positive differences in migrant students’ education.